Evaluasi SPI (Sistem Pengendalian Internal) Pengadaan Obat Berdasarkan Dana Blud - Permatasari, Sellvy Dian (Universitas Multi Data Palembang, 2024)
This study aims to evaluate the intern control system of drug procurement based on BLUD funds. The descriptive qualitative method was used with data sources in the form of interviews, observations and documentation at dr. Moewardi Surakarta Regional General Hospital (RSDM). The flow of drug procurement both conventional and E-Purchasing ISP is presented through a flowchart, and this intern control system evaluation emphasizes the COSO (Committee of Sponsoring Organizations) concept. Although the flow of drug procurement is in accordance with applicable policies and regulations and the results show that this intern control system is appropriate, there are still shortcomings that require improvement. The conclusion of this study is that RSDM needs to strengthen intern controls to prevent potential irregularities, providing a foundation for increasing effectiveness in meeting drug needs according to applicable procedures. This evaluation is a guide for improving the intern control system to achieve organizational goals more efficiently.